THE IMPORTANCE OF TRIZ TECHNOLOGY IN DEVELOPING THINKING SKILLS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Formation of skills such as inventiveness and modeling in elementary school students is becoming a modern demand. TRIZ technology is the technology that is suitable for the development of these two abilities. This article talks about the methods and methods of using TRIZ technology in elementary school students.